On the distribution of sequences of the form $(q_ny)$ - Kristensen, Simon; Persson, Tomas (MATHEMATICA SCANDINAVICA, 2025)
We study the distribution of sequences of the form $(q_ny)_{n=1}^∞ $, where $(q_n)_{n=1}^∞ $ is some increasing sequence of integers. In particular, we study the Lebesgue measure and find bounds on the Hausdorff dimension of the set of points $γ \in [0,1)$ which are well approximated by points in the sequence $(q_ny)_{n=1}^∞ $. The bounds on Hausdorff dimension are valid for almost every $y$ in the support of a measure of positive Fourier dimension. When the required rate of approximation is very good or if our sequence is sufficiently rapidly growing, our dimension bounds are sharp. If the measure of positive Fourier dimension is itself Lebesgue measure, our measure bounds are also sharp for a very large class of sequences.